Bifunctional Co‐based Catalysts for Fischer‐Tropsch Synthesis: Descriptors Affecting the Product Distribution. Issue 11 (4th May 2021) - Straß‐Eifert, Angela; van der Wal, Lars I.; Hernández Mejía, Carlos; Weber, Lennart J.; Yoshida, Hideto; Zečević, Jovana; de Jong, Krijn P.; Güttel, Robert
Abstract: The conversion of synthesis gas to hydrocarbons in the Fischer‐Tropsch (FT) synthesis suffers from a broad product distribution not directly providing high fuel quality. This work, therefore, aims at bifunctional catalysts combining the FT and hydroprocessing (HP) reaction for tailoring the product spectrum. Therefore, we applied a bottom‐up synthesis strategy for bifunctional cobalt/zeolite catalysts and investigated the obtained materials by advanced characterizations such as 3D TEM tomography. Based on the results, descriptors are defined for the acidity and the porosity, which are varied by changing the material preparation parameters. The catalytic properties of the obtained materials are studied in FT experiments at industrially relevant conditions (20 bar, 240 and 260 °C) and are correlated to the material properties by means of the respective descriptors. Therefore, the product distribution was analyzed in detail and distinguished between n‐paraffins and 1‐olefins as typical FT‐products as well as paraffinic and olefinic isomers formed in the HP classified in different fractions. It was found that, apart from the acidity, the pore structure plays a vital role in primary and secondary cracking/isomerization reactions. In addition to that, the particular 3D pore structure and thus the individual transport trajectories of the FT products are strongly affecting the cracking and isomerization probability and consequently the product distribution. Abstract : Fischer‐Tropsch synthesis : The properties of Co/zeolite bifunctional catalysts were correlated to the product distribution in Fischer‐Tropsch synthesis. It is observed that both the acidity and the pore structure play a vital role in primary and secondary hydrocracking/isomerization reactions.